Graphical user interface for statistical characteristics of skull morphology in syndromic craniosynostosis - Satari, Siti Zanariah; Zulkipli, Nursyahirah; Wan Yusoff, Wan Nur Syahidah; Hariri, Firdaus; Abdullah, Norli Anida; Hussin, Abdul Ghapor (2021)
Circular data, such as skull angle can be found in biomedical area. Biomedical data are often complex in structure and exposed to an abnormality. In this study, we consider a case study related to a congenital disorder called craniosynostosis syndrome which results in skull growth abnormalities. In this study, 12 skull angles of craniosynostosis patients age of 0-12 years old in Malaysia are analysed using circular statistics methods. The raw CTSCAN data is provided by UM Specialist Centre. The statistical characteristics of skull morphology in syndromic craniosynostosis are displayed and compared with the normal skull data of Malaysian children age 0-12 years old. A Graphical User Interface (GUI) is developed using Python to give user a specific statistical analysis about the skull morphology characteristics of craniosynostosis syndrome patients in Malaysia.